â€œMARKETING 101: TIKTOK MARKETING FOR YOUR BUSINESSâ€ DI ALFALAND GROUP INDONESIA - Riza, Fahrul (Business Management Journal, 2022)
The use of social media as a tool to support business activities is increasingly popular among companies. The survey from AppAnnie claims that TikTok has become the most downloaded social media since 2018 replacing Instagram. Its algorithmic ability to catch user preferences and short content duration make TikTok an attractive social media to various age segments. This community service activity entitled " Marketing 101: TikTok Marketing for Business " was carried out collaboratively between the Bunda Mulia University Management Study Program and Alfaland Group, a company that is engaged in the property management sector. The implementation of Community Activity Restrictions (PPKM) is a serious challenge for the service company to maintain their revenue. The purpose of this activity is to provide training to employees of the operational and marketing division of PT Alfaland about how to use TikTok as a marketing tool. The training was conducted online and was attended by employees from branches located across provinces in Indonesia. The training materials presented included: an introduction to the TikTok application and measurement tools to monitor the effectiveness of marketing. The output of this service was the production of creative content created by participants to market products and services from Alfa-land; increasing the creativity of employees, especially the operational and marketing divisions in marketing services from AlfaLand. Feedback received from employees related to using the TikTok application for marketing includes flexible cost control; can monitor the viewer in real-time; audience targeting, and monitoring feedback from customers.